Technology dynamics : the generation of innovative ideas and their transformation into new technologies - Bonomi, Angelo (Boca Raton, FL : CRC Press, 2020)
"The book describes the complex activity of technology innovation, the process of generation of innovative ideas, and their transformation into new technologies. It assumes that technology evolves continuously, is changed by innovations, and is characterized by a dynamics constituted by technological processes occurring in organizational structures. It is aimed at managers developing strategies for technology innovation, researchers interested in exploiting scientific results for innovative ideas and new technologies, and students studying economics of innovation. The book is of interest to private or public financiers of innovation and policy makers involved in economic growth strategy"--
OCLC-licensed vendor bibliographic record.
Keywords: Technological innovations -- Management; TECHNOLOGY / Engineering / General; TECHNOLOGY / Inventions